Clinical and angiographic profile of premature heart attack in patients with family history of premature coronary heart disease: A substudy of the PCAD registry (Registered under the Clinical Trials Registry of India [CTRI/2018/03/012544]) - Rahul S Patil; C M Satvic; Laxmi H Shetty; H S Natraj Setty; Spandana Komma; Anesh Rajesh Jain; T R Raghu; C N Manjunath (Research in Cardiovascular Medicine, 2020)
Aim: The aim is to study the clinical, social, biochemical, and angiographic profile of youth (under 35 years) with familial premature coronary artery disease (PCAD). Subjects and Methods: The PCAD registry is a prospective ongoing descriptive observational study of Indians aged below 40 years with coronary artery disease (CAD) which was started on April 1, 2017. Of 3450 patients registered in the PCAD registry till date, 1628 patients were aged 35 years or younger. Of these 1628 patients, 218 satisfied entry criteria. The entire clinical and angiographic profile of these patients was documented. The distribution of different lipid profile parameters was visualized by nonparametric density plot. The data were analyzed by statistical software R version 3.5.0. Results: Of 3450 patients registered in the PCAD registry till date, 1628 patients were aged ≤ 35 years. Two hundred and eighteen out of these 1628 patients (13.39%) belonged to the study group for this particular study. The mean age of all patients under the PCAD registry was 30.44 years, and 201 (92.2%) were males. 106 (48.62%) were smokers. Twenty-nine patients (13.33%) of them were diabetic. The most common index presentation of CAD in familial PCAD was with ST-elevation myocardial infarction (STEMI; 112 patients – 51.37%) and unstable angina/non-STEMI (58 patients – 26.6%). Forty-eight patients (22.01%) presented with evolved MI. Conclusions: Almost 14% of coronary events in younger age (under 35 years) were attributable to family history of CAD. Family history of CAD can be used as a criterion to select younger age population to perform targeted screening for cardiovascular diseases.